Big Five personality and mind wandering in athletes: mediating role of trait anxiety - Li, Y.; Ma, J.; Xi, Y.; Li, J. (Frontiers in Psychology, 2024)
Objective: Mind wandering is a common phenomenon among athletes during training and competition, and can lead to poor performance. We attempt to clarify which personality type is more prone to mind wandering and the role of trait anxiety between them.